RETRACTED: Real time thermal imaging monitoring based on object detection in the design of physical education auxiliary system: Computational thermal modeling - Ben, Liu; Junkai, Feng (Thermal science and engineering progress, 2025)
This article has been retracted: please see Elsevier policy on Article Correction, Retraction and Removal (https://www.elsevier.com/about/policies-and-standards/article-withdrawal). This article has been retracted at the request of the Editors-in-Chief. Post-publication, an investigation conducted by the editors discovered that the peer-review process for this article was compromised. Specifically, the editors have identified issues that raise significant doubts about the objectivity and thoroughness of the reviews conducted. The editors have determined that the integrity of the peer-review process has been undermined, leading to a loss of confidence in the validity of the findings presented in the article, and made the decision to retract. Apologies are offered to the readers that this was not detected earlier.